2021
DOI: 10.32735/s2735-65232020000277
|View full text |Cite
|
Sign up to set email alerts
|

Autoconcepto y rendimiento académico: una revisión de la Literatura Hispana

Abstract: El presente artículo corresponde a una revisión de veinte investigaciones centradas en indagar las diversas relaciones existentes entre autoconcepto y desempeño académico. La búsqueda se enfocó en estudios publicados en lengua castellana presentes en diversas bases de datos. La organización de la información consideró como criterio la categorización de los participantes. Los resultados apuntan a que los estudios en general evidencian relaciones entre autoconcepto y rendimiento académico, donde el autoconcepto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(11 reference statements)
1
1
0
1
Order By: Relevance
“…Considering the multifactorial nature of AP, the present research analyzes the relationship between intense physical activity and the personal variables of attention, concentration, academic self-concept, and the social variable of the social environment through the basic psychological needs variable that encompasses the dimensions of autonomy, relationship satisfaction, and competence satisfaction. In line with other research, this study also found that AP positively correlates with the “relatedness” dimension of basic psychological needs [ 56 , 57 , 59 ], academic self-concept [ 48 , 49 , 50 , 51 ], and moderate-to-vigorous physical activity outside of school. These findings suggest that maintaining relationships with others, having a high academic self-concept, and engaging in vigorous physical activity may influence students’ academic performance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Considering the multifactorial nature of AP, the present research analyzes the relationship between intense physical activity and the personal variables of attention, concentration, academic self-concept, and the social variable of the social environment through the basic psychological needs variable that encompasses the dimensions of autonomy, relationship satisfaction, and competence satisfaction. In line with other research, this study also found that AP positively correlates with the “relatedness” dimension of basic psychological needs [ 56 , 57 , 59 ], academic self-concept [ 48 , 49 , 50 , 51 ], and moderate-to-vigorous physical activity outside of school. These findings suggest that maintaining relationships with others, having a high academic self-concept, and engaging in vigorous physical activity may influence students’ academic performance.…”
Section: Discussionsupporting
confidence: 92%
“…García Perales et al [ 50 ] indicated that the general and academic self-concept of primary school students positively correlates with academic performance, indicating that a positive self-perception influences better school performance. In the systematic review by Mansilla Chacon et al [ 51 ], the relationship between self-concept and AP was analyzed. In their study, it can be observed that primary and secondary school students with a high academic self-concept are linked to better AP, especially in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Conseguir una calificación de sobresaliente (9-10) en la asignatura de Educación Física influye positivamente en la mayoría de escalas de Autoconcepto Físico y de actitudes y percepciones respecto a la disciplina de educación física. La nota puede ser una herramienta para valorar el proceso de los alumnos/as, especialmente ya que refleja el nivel de consecución de las competencias u objetivos establecidas en el currículo (Zulaika, 2005;Alcaide, 2020;Camuñas & Alcaide, 2020;Gracia, 2020;Infantes, 2021;Mansilla-Chacón, 2021;Rebolledo-Mejía et al, 2021;Obed Amoah et al;Mohd Zaini et al, 2021). Asimismo, es asombroso que en la mayoría de las titulaciones las puntuaciones adquiridas en educación física estén por encima del 8 ¿Cómo se califica en educación física?…”
Section: Discussionunclassified